Cervical cancer in Central and South America: Burden of disease and status of disease control. (September 2016) - Murillo, Raúl; Herrero, Rolando; Sierra, Mónica S.; Forman, David
Highlights: Cervical cancer remains a major public health problem in Central and South America. However, several countries in the region have reduced cervical cancer mortality. Most countries require significant improvements in screening program organization. HPV vaccination is a major opportunity for cervical cancer control given limitations in screening. The availability of population-based data benefits program evaluation. Abstract: Rationale and objective: More than 20 years after cytology-based screening was introduced in Central and South America (CSA), cervical cancer remains a leading cause of cancer incidence and mortality in the region. Although several population-based registries exist in the region, few comprehensive analyses have been conducted to describe the status of cervical cancer control. Methods: Population-based data from cancer registries in 13 countries and mortality data from 18 countries in CSA were analyzed. Standardized incidence and mortality rates were estimated and time trend analysis performed when information was available. In addition, a search of available data on HPV vaccination and cervical cancer screening was carried out. Results: Cervical cancer incidence and mortality have decreased in some CSA countries, with an annual percentage change from −4.2 to −6.7 for incidence and −0.2 to −8.3 for mortality. In total, seven countries have age-standardized mortality rates over 10 per 100, 000 women, generally corresponding to those with the lowest income levels. All countries have implemented screening programs with different extents of coverage and levels of organization. To date, nine countries have introduced HPV vaccination in national immunization programs. Conclusions: Despite incidence declines observed in some countries, cervical cancer mortality remained almost stable in most countries in the region. Decreases in mortality trends in Chile and Costa Rica are probably the result of early detection programs. Better organized programs might favor greater impact on cancer incidence and mortality, but technological developments offer more suitable opportunities for prevention and alternative approaches for screening of precancerous lesions.